1995
DOI: 10.1111/j.1365-2052.1995.tb02662.x
|View full text |Cite
|
Sign up to set email alerts
|

Number and distribution of silver‐stained nucleolar organizer regions and evolutionary relationships in domestic pigs

Abstract: Variation in the numbers of silver-stained nucleolar organizer regions (Ag-NORS) were examined in 36 breeds of domestic pig of different geographic origins and five subspecies of wild boar. The relationship between Ag-NORs and evolution of domestic pigs was investigated. In all pigs observed, Ag-NORs were localized on the secondary constriction of chromosomes 10 and 8. The mean Ag-NOR numbers varied from 2.0-4.0, and decreased gradually with the different geographical distribution from south to north in China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Cytogenetic studies have shown that NORs are useful tools in many kinds of animal research, from NORs localization and polymorphism to the relationship between breeds and species (Liu et al 1995;Zijlstra et al 1997;Schempp et al 1998;Danielak-Czech et al 1999;Santani et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic studies have shown that NORs are useful tools in many kinds of animal research, from NORs localization and polymorphism to the relationship between breeds and species (Liu et al 1995;Zijlstra et al 1997;Schempp et al 1998;Danielak-Czech et al 1999;Santani et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . [ 24 ] stated that the polymorphism of Ag-NORs in pigs is caused mainly by differences in frequency of silver deposits on chromosome 8.…”
Section: Resultsmentioning
confidence: 99%
“…RH FW map length for a given region is influenced by marker density; the higher the marker density, the longer the map length (cR); thus, the higher the map resolution. A second is the localization of the NORs, or the ribosomal RNA genes (RNR, or rDNA) on SSC10p near the centromere [ 31 - 34 ]. SSC10 is one of two chromosomes (the other one is SSC8) in the porcine genome that harbors ribosomal RNA genes (RNR, or rDNA) in NORs located in the proximal region of SSC10p near the centromere.…”
Section: Resultsmentioning
confidence: 99%
“…SSC10 is one of two chromosomes (the other one is SSC8) in the porcine genome that harbors ribosomal RNA genes (RNR, or rDNA) in NORs located in the proximal region of SSC10p near the centromere. Silver-staining (Ag-NOR) indicates that the porcine RNR genes on SSC10 are constitutively active in all pig breeds, while their activity on SSC8 varies among different pig breeds [ 31 ]. The ratio of FW vs. non-FW markers was 1:4 (3 FW/12 non-FW) in the NOR region (Fig.…”
Section: Resultsmentioning
confidence: 99%